Genossenschaften im Wettbewerb - Reichel, Richard; Voigt, Kai-Ingo (Unternehmen im Wettbewerb - Gedenkschrift für Wilfried Feldenkirchen (1947-2010), 2020)

The effect of a partnership franchising model on consumer satisfaction for a large German cooperative retail chain before and during the COVID-19 pandemic: Die Auswirkung eines Partnerschafts-Franchising-Modells auf die Verbraucherzufriedenheit einer großen deutschen genossenschaftlichen Einzelhandelskette vor und während der COVID-19-Pandemie - Bachmann, Severin; Reichel, Richard; Wrede, Matthias (Zeitschrift für das gesamte Genossenschaftswesen, 2023)
Using web reviews, we analyze the effect of a partnership franchising model on consumer satisfaction and the differences in these effects before and during the COVID-19 pandemic for one of the largest German retailers. The franchise model of this chain is special in that the franchisor participates financially in a partnership model, and on the other hand, the franchisees enjoy significant entrepreneurial freedom. This study finds that consumers are substantially more satisfied with franchisees than centrally managed stores. Consumer satisfaction declined and the lead of franchisees diminished during the pandemi
Keywords: cooperatives; franchise; consumer satisfaction; retail; COVID-19; pandemic